Charlotte Smith and the Sonnet Form, Place and Tradition in the Late Eighteenth Century - Roberts, Bethan (Book collections on Project MUSE., 2019)
"Exploring Charlotte Smith's Elegiac Sonnets, author Bethan Roberts clarifies their 'place', understood in multiple ways, in literary history. It argues that Smith's work engages more deeply with tradition than has hitherto been realised and revises our understanding not only of Smith's career but also of the sonnet in eighteenth-century England"--